Tanggapan Peserta Didik terhadap Pendekatan Pembelajaran Kontekstual oleh Instruktur di Bimbingan Belajar Al-Rasyid Education Lubuk Alung - Sri Desy Sylvia Dinda; Vevi Sunarti (Universitas Negeri Padang, 2018)
This research is motivated by the contextual learning approach used by instructor at the Al-Rasyiid Education Tutoring Lubuk Alung in formulating learning materials and the use of interesting and not boring learning models, which are characterized by learning outcomes obtained by students. This type of research is quantitative descriptive. The population in this study was 30 students in Al-Rasyiid Education tutoring. The study sample was taken 22 people. Technical data analysis uses quantitative descriptive techniques with percentage tracking. The results of the study found that (1) students 'responses to the formulation of learning materials used by instructors were categorized as good (2) students' responses to the use of learning models used by instructors were categorized as good. Keywords: Tutoring, Contextual Learning Approach